THE DEVELOPMENT OF BANK INNOVATIONS IN MODERN CONDITIONS - E. Shikova (Publishing House of the State University of Management, 2016)
In the article the analysis of factors influencing the efficiency of innovative processes in the banking sector. Define the levels based on their types and forms of implementation to identify different approaches for implementing the various activities. Shows the interaction and organization of work with innovation in the Central office of Sberbank.